Duración del desarrollo y estadísticos poblacionales de Capulinia sp. cercana a jaboticabae von Ihering (Hemiptera: Eriococcidae) sobre varias especies de Psidium - Chirinos, Dorys T; Geraud-Pouey, Francis; Romay, Gustavo (ENTOMOTROPICA, 2007)
Capulinia sp. is a new species and the scarce available information points toward its neotropical origin, probably Amazonian. Survival, fertility and populations statistics were evaluated on guava selections, Psidium guajava L, [Criolla Roja (CR), Selección 12 (S12) ] and on other species: P. friedrichsthalianum Berg.-Niedenzu y P. guineense Swartz during June-October 1999 to estimate host plant amplitude and favorability of the guava accessions to the insect. The ranking of host plants with respect to survival of Capulinia sp. was: on P. guajava CR>S12>P. friedrichsthalianum>P. guineense. The lower survival on S12 as compared with CR was due to the scarcity of bark exfoliations on the former. High mortality on P. friedrichsthalianum and P. guineense could be associated with biochemical factors and suggests Capulinia not evolved on those. High survival (90%) and fertility (2639.80Â±161.43 eggs/female) of Capulinia on CR and population statistics (Ro :1090.81, T:45.37 y rm:0.20) explain the high infestations that occurred in the absence of efficient natural enemies when the insect colonized new areas. This capacity for population development partially supports the importance Capulinia reached as guava pest in Venezuela. The effect of bark physical features and plant biochemestry could constitute sources for resistance in search for lowering incidence and damages by Capulinia sp.